Drug repurposing in traditional Chinese medicine: from empirical wisdom to modern therapeutic strategies - Wu, Yuan; Huang, Jiarong; Guo, Jiajun; Lian, Wanming; Suo, Maorong (Frontiers in Pharmacology, 2025)
Traditional Chinese medicine (TCM), with its multi-component and multi-target nature, offers rich potential for drug repurposing. Advances in systems biology, computational modeling, and high-throughput technologies have enabled systematic analysis of TCM mechanisms, facilitating in the identification of active ingredients, target interactions, and synergistic effects. However, most existing reviews focus on individual methods rather than providing an integrative translational strategy tailored to the complexity of TCM. This review addresses that gap by proposing a stage-based framework that combines mechanism analysis, preclinical validation, and clinical translation. We highlight key methodologies such as network pharmacology, multi-omics, molecular docking, and phenotypic screening, and discuss how they can be synergistically applied. Emerging technologies including AI, big data, 3D bioprinting, and organoid models are evaluated not only for their utility but also through critical analysis of their limitations in capturing TCM’s holistic principles. By bridging traditional knowledge with modern biomedical innovation, this review offers a novel roadmap for accelerating evidence-based TCM repurposing. The proposed integrative strategy supports more reproducible, mechanistically grounded, and globally relevant applications of TCM in modern drug development.